Women's Leadership in Creating Change, Synergy, and Empowering Human Resources in Madrasah - Junaidah, Junaidah; Haryani, Dwi; Fanisyah, Elsah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Women's leaders have begun to play an active role in organizational activities in various fields, including education. Therefore, this study aims to analyze women's leadership in creating change, synergy and empowering existing human resources in madrasas using a descriptive and qualitative approach. This study used data collection techniques through interviews, observation, and documentation. Data analysis is divided into three current flows of activity: data reduction, data display, and concluding. According to the findings of this study, women leaders lead in several ways, including creating change by applying several principles of being open, insightful, and skilled; being disciplined, authoritative, and responsible; engaging in routine observation and discussion; and improving quality by participating in training. Furthermore, by creating synergy by applying the principle of cooperation and involving all human resources in decision-making that is consistent with decisions and policies, Then, in empowering human resources, women leaders apply the principles of assigning tasks and responsibilities according to competence, collaborating, granting autonomy, and facilitating human resources so that they are freer to develop themselves, especially those related to improving the quality of their learning activities. Based on these findings, this study is expected to serve as a model for women leaders to follow to become quality leaders.